Влияние водного стресса на посевные качества семян и урожайность озимой пшеницы - Yu. G. Skvortsova; G. A. Filenko; T. I. Firsova; V. L. Gaze; N. N. Anisimova (Зерновое хозяйство России, 2018)
The effect of water stress on quality and productivity of winter wheat seeds The article presents the study results of water stress effect on quality and productivity of winter wheat seeds. The moisture supply of plants affects the growth power and field germination of seeds. The decrease of the index has no significant effect on the laboratory germination, as it does not fully reflect the quality of the seeds. The varieties ‘Asket’, ‘Don 93’ and ‘Izyuminka’ showed the minimum decrease of 1000-kernels weight under the stress conditions on 24%, 25% and 27% respectively. The variety ‘Aksiniya’ showed the maximum decrease of this trait (40%). The variety ‘Asket’ has shown the increase of sprouts number (30% FG) in comparison with the standard variety (70% FG). The variety ‘Ermak’ has shown a slight decrease of field germination (on 2%) and the variety ‘Lilit’ has shown a large decrease of field germination (on 17%) in comparison with the standard variety. The conducted study determined that the varieties of winter soft wheat had a different reaction during germination in the conditions of artificial drought. The quality of seeds grown in dry conditions have lower indexes in comparison with the optimal growing conditions, excluding the variety ‘Asket’ that surpassed the indexes of growth power (on 2%) and field germination (on 1%) compared with the control variety.